Pengaruh Bullying Terhadap Perkembangan Belajar Peserta Didik Di Sekolah Dasar - Theodosius Davis Prasetya; Tiara Sari; Dea Ajeng Ayuningtyas; Sri Suwartini; Sindi Novita Putri (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
Bullying in elementary schools is a persistent issue that significantly affects students’ psychological well-being, social interaction, and academic development. This study aims to identify the various forms of bullying occurring in elementary school settings, analyze their impact on students’ learning development, and describe the roles of teachers and the school environment in preventing and addressing bullying behavior. This research employs a qualitative descriptive method through a literature review of scientific articles and research findings published in recent years. The analysis reveals that physical, verbal, and psychological bullying can lead to emotional disturbances such as anxiety, low self-esteem, and stress, which subsequently reduce students’ learning motivation and academic performance. Furthermore, the presence of bullying disrupts the school climate, making the learning environment unsafe and less conducive for healthy social interaction. Teachers play a crucial role in early detection, intervention, and the creation of an inclusive and empathetic school culture. Therefore, collaborative efforts among teachers, schools, and parents are essential to establish a safe, supportive, and positive learning environment that fosters students’ holistic development.